Analisis Tingkat Kepuasan Menggunakan Metode End User Computing Satisfaction (EUCS) - Kecitaan Harefa (Jurnal Informatika Universitas Pamulang, 2022)
User satisfaction is one of the most important factors for the successful implementation of information systems, including academic information systems in tertiary institutions. The academic information system at the Polytechnic has never been evaluated for user satisfaction, so there may be obstacles in its use. Since the implementation of this academic information system, several problems have been found, such as incorrect grades entered, some functions not running optimally, information is rarely updated, sometimes the server goes down, so the system cannot be used. The problem encountered may be due to an academic information system whose satisfaction factor has never been evaluated based on the end user's perception. As a result, the system does not meet the end user's needs and expectations so they are not very satisfied with using it. The purpose of this study is to measure the quality of academic information systems and determine user satisfaction. The model used in this study is End User Computer Satisfaction (EUCS) which consists of five factors, namely Content, Accuracy, Format, Ease of use, Timeliness as the independent variable and satisfaction as the dependent variable. The sample in this study was 146 respondents consisting of students. Data collection used a closed questionnaire consisting of 13 questions for the five variables studied. The results of this study were obtained based on data analysis carried out using descriptive analysis techniques using a range of categories and percentages via a Likert scale. The results of this study indicate that the level of satisfaction of users of academic information systems at Polytechnics as a whole is included in the agree category. Users feel satisfied using the Polytechnic academic information system, with a percentage value of 76.43%.